Daya Krishna and twentieth-century Indian philosophy : a new way of thinking about art, freedom, and knowledge - Raveh, Daniel (London, England : Zed Books, 2020)
"Daya Krishna and Twentieth-Century Indian Philosophy introduces contemporary Indian philosophy as a unique philosophical genre through the writings of one its most significant exponents, Daya Krishna (1924-2007). It surveys Daya Krishna's main intellectual projects: rereading classical Indian sources anew, his famous Samvad Project, and his ardent attempt to formulate a social and political theory that can better fit India's needs and challenges. Conceived as a dialogue with Daya Krishna and contemporaries, including his interlocutors, Krishnachandra Bhattacharyya, Badrinath Shukla, Ramchandra Gandhi and Mukund Lath, this book is an engaging introduction to anyone interested in contemporary Indian philosophy and in the thought-provoking writings of Daya Krishna"--
Toward a new picture of Indian philosophy -- Thinking creatively about the creative act : a dialogue with Daya Krishna -- Freedoms -- concepts and actions : Daya Krishna and social philosophy.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Krishna, Daya; Indic philosophy -- 20th century; Non-Western philosophy; Electronic books